The Effect of Household Type on Income Inequality: Evidence from the EU-15 Countries - Joanna MUSZYNSKA; Ewa WEDROWSKA (Communications of International Proceedings, 2020)
Specialist literature presents multiple factors that are believed to affect income inequality. Our study focuses on household type as a determinant of overall inequality since it employs household as the unit of analysis, and examines the extent of inequality among households by incorporating household income data. Therefore, apart from assessing the level of income inequality, the aim of the study is to verify the extent to which household type affects household income inequality. Moreover, we endeavour to answer the question of whether there exists any common pattern of the influence of household type on income inequality. Our study aims at expanding and updating the knowledge regarding the dimensions of household income inequality in European countries. We employ the latest available representative microdata derived from the EU-SILC study. This study builds upon the Mean Logarithmic Deviation (Theil L index) and its property of being additively decomposable to assess the effect of household type on household income inequality. Our results indicate that households in the EU-15 countries differ in structure, with the most noteworthy differences occurring between the Mediterranean and the Nordic countries. The situation of households run by a single parent is on average worse than in case of other households. Generally, households run by couples without children or couples with one or two children are best-off. The effect of differences in household structure on income inequality is the most noteworthy in the Nordic and in the Anglo-Saxon countries, while in Luxemburg and the Mediterranean region this effect is the least notable.
Keywords: Income Inequality; Household Type; Mean Logarithmic Deviation; Theil Index L; Gini Coefficient